(3eSfO GdHRGQs - (3CHh HcQ CMeO Hf YeQh Hf YHO GdNGdb GdHRGQ,J (B292 (3g` s ((3eMeO Hf EHQGgje GdeTOGdi s)
(3ChdgG (B:s
(3Chd GdehLhO efg CKfGA eSfO CHj HcQ GdUOjb QVi Gddg Yfg Hbhdg (B: (3heeG Qhi Ydi Hf CHj WGdH s
(3BNQgG (B:s
(3Cf QShd Gddg Udi Gddg Ydjg hSde , bGd (B: (3NjQ GdCfUGQ Hfh GdfLGQ (B: (3ced GdSaQ GdChd ef eSfO GdHRGQ HYddg HJdhg ai GdSaQ GdKGfi Ef TGA Gddg JYGdi ef MOjK CHj GdjSQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B189s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs